Design and optimization of pi-slotted dual-band rectangular microstrip patch antenna using surface response methodology for 5G applications - Lijaddis Getnet Ayalew; Fanuel Melak Asmare (Heliyon, 2022)
Modern wireless network antenna technologies are designed to meet the ever-increasing needs of emerging applications. Hence this paper investigates potential antenna impedance bandwidth performance enhancement techniques based on optimizing independent geometrical parameters of pi-shaped slotted dual-band rectangular microstrip patch antenna (DBRMSPA). The antenna considered in the optimization process is with a slotted patch which improves impedance bandwidth of the antenna. And independent factors are geometrical parameters that influence the antenna's impedance bandwidth (BW) and operating frequency (Fr). The factors are substrate height (Hs), patch length (L), and slot (s2) length (Ls), and the experiment is designed using Computer Simulation Technology (CST) suite 2019 to generate a dataset by varying these parameters in a specific range. Then based on the dataset, response surface methodology (RSM) is applied to develop mathematical models that relate the responses Fr and BW with independent variables. Using analysis of variance (ANOVA), the effects of varying independent factors on both responses and model validation were investigated. Then constrained numerical optimization is applied to determine optimum design parameters. The optimized parameters, substrate height, patch length, and slot (s2) length (Ls) are 0.648 mm, 3.048 mm, and 1.325 mm, respectively. The optimized dual-band antenna, designed with optimized parameters, achieved a target impedance bandwidth (≥4 GHz), 7.2 GHz and 4.17 GHz at 28 GHz and 38 GHz, respectively. Similarly, the antenna's radiation efficiency at 28 GHz and 38 GHz is 75.457% and 88.6237%, respectively. The proposed antenna also gives a gain of 6 dBi at 28 GHz and 4.15 dBi at 38 GHz. And VSWR is less than 2 throughout its impedance bandwidth. All of these results were generated using the CST EM solver and validated using the Ansys High Frequency Simulation Software (HFSS) with good agreement. As a result, the proposed potential performance enhancement techniques provide an antenna with a wide impedance bandwidth suitable for 5G mobile communication applications.